Verbalization of Bacchic Actions in the Artistic World of Fyodor Abramov - O. A. Dimitrieva (Научный диалог, 2020)
The features of verbalization of Bacchic actions in the works of Fyodor Abramov (tetralogy “Brothers and Sisters”, novels “Pelageya”, “Alka”, “Mamonikha”, “Wooden Horses” and stories) are considered. The linguistic means of the individual author’s interpretation of the “Wine Drinking” sphere as a fragment of the semantic field of a literary text are analyzed. Bacchic action from the point of view of manifestation of one or another cultural semantics in it (according to M. L. Kovshova): utilitarian, functional, aesthetic, social hierarchical, ideological and spiritual is studied. It is noted that in the artistic world of Abramov, the utilitarian and functional aspects generally correspond to the general cultural ones, reflected in the paremias. It was revealed that the social-hierarchical cultural layer has its own specificity, which manifests itself in two oppositions: “village — city”, “collective farmer-peasant — rural intellectuals”. The author notes that the ideological and spiritual component in understanding the situation of wine drinking is associated with the expression of the author’s attitude, his worldview through the prism of the character’s opinion. It is concluded that the verbalization of Bacchic action is distinguished by figurative interpretation, the attraction of components from various spheres: the use of expressions containing somatisms, animalisms, perceptual vocabulary, verbs of physical impact, etc. When analyzing the social component of some Bacchic expressions, it is noted that the objects of wine drinking (vessels) are interpreted as subjects of interpersonal relationships.